A Closer Look on Indonesian EFL students’ Writing Process: The Application of Cognitive and Metacognitive Strategies - Azizah, Safira; Soraya, Soraya (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2023)
Cognitive and metacognitive strategies have been researched to find an effective strategy in teaching writing. However, little attention has been given to investigate what is on the students’ minds while applying those strategies in the writing process. This descriptive qualitative study aims to investigate the process of applying the cognitive and metacognitive strategies by EFL students while performing argumentative essays. Three university students of the English Department taking the Essay Writing subject were invited to record the process of authoring argumentative essays using Zoom recording to display full audio and video on screen. Their writings were checked and the students were interviewed. This process used think-aloud protocols (TAPs) completed with the screen recording method (SRM) to record all activities on the computer screen, students’ work, and the interview explored the learners’ perception towards particular situation in their writing process. The data were categorized and analyzed using English as a foreign language (EFL) writing strategies as a framework for narrative analysis. This study found that both cognitive and metacognitive strategies helped all participants complete their essay through the thinking process and decision making of each step and strategy. While cognitive and metacognitive were applied distinctively in each participant’s writing processes, it produced the internalization of writing steps critically in self-regulated learning. This study demonstrates that cognitive and metacognitive processes are effective in promoting varied writing strategies and self-regulated learning for EFL learners. To get a thorough application of cognitive and metacognitive strategies in writing activity, future research can use other genre for students at different age or level of education.